Semiotic Analysis of Social Class Representation in Satria Dewa Gatotkaca Movie: Analisis Semiotika Representasi Kelas Sosial dalam Film Satria Dewa Gatotkaca - Hidayatullah, Barriman; Hariyanto, Didik (House of Wisdom: Journal on Library and Information Sciences, 2025)
The study aims to analyze the representation of social class in the film "Satria Dewa: Gatotkaca" using a qualitative approach and Roland Barthes' semiotic analysis. The research methodology adopts a descriptive qualitative approach. Data were collected through three main methods: (i) a comprehensive observation of the film to understand its content and nuances; (ii) documentation, where the researcher selected and highlighted images of scenes depicting the representation and social class of Kurawa and Pandawa in the series; and (iii) a literature review of various sources such as theses, journal articles, websites, the internet, and relevant books. The collected data were then analyzed using Roland Barthes' semiotic approach. The analysis revealed four aspects related to the signs in the film: different lifestyles, differences in attire, unconscious social class boundaries, and class identity influenced by royal lineage. Highlights: Lifestyle: The difference in lifestyle depicts the difference in social class between the Pandavas and the Kuravas. Clothing: Clothes reflect social status and class differences. Lineage: Class identity is linked to royal lineage which affects social status. Keywords: Representation, Roland Barthes, Semiotic, Social Class